Inclusion (HBR emotional intelligence series., 2023)
"We all want our colleagues to feel safe, heard, and free to be their authentic selves at work. But being an inclusive colleague doesn't happen overnight-it's an evolving process that involves growing, learning, and intentional effort. This book will teach you how to address and understand your biases, how to get better at noticing and responding to microaggressions, and why being an inclusive colleague will spark more-productive and -rewarding relationships with your coworkers and boss. With the latest psychological research and practical advice from leading experts, you'll learn how to make your workplace more inclusive and culturally competent-starting with yourself"--